2014
DOI: 10.1124/jpet.113.211144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isoflurane on Myocardial Energetic and Oxidative Stress in Cardiac Muscle from Zucker Diabetic Fatty Rat

Abstract: The effect of inhalational anesthetics on myocardial contraction and energetics in type 2 diabetes mellitus is unknown. We investigated the effect of isoflurane (ISO) on force and intracellular Ca 21 transient (iCa), myocardial oxygen consumption (MVO 2 ), and energetics/redox behavior in trabecular muscles from Zucker diabetic fatty (ZDF) rats. At baseline, force and corresponding iCa were lower in ZDF trabeculae than in controls. ISO decreased force in both groups in a dosedependent manner. ISO did not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…GSH was determined with 50 M monochlorobimane (MCB), a membrane-permeant indicator of GSH (2). Trabeculae were loaded with 7 M CM-H 2-DCFDA and 2 M MitoSOX dissolved in 0.4% pluronic acid F-127, 0.1% DMSO, 5g/l cremophor, and 1 M N,N,N=,N= tetrakis (2-pyridylmethyl)ethylenediamine (48,52).…”
Section: Methodsmentioning
confidence: 99%
“…GSH was determined with 50 M monochlorobimane (MCB), a membrane-permeant indicator of GSH (2). Trabeculae were loaded with 7 M CM-H 2-DCFDA and 2 M MitoSOX dissolved in 0.4% pluronic acid F-127, 0.1% DMSO, 5g/l cremophor, and 1 M N,N,N=,N= tetrakis (2-pyridylmethyl)ethylenediamine (48,52).…”
Section: Methodsmentioning
confidence: 99%
“…Among various comorbidities in diabetic patients, coronary heart diseases is linked with stroke and early death. Interestingly, isoflurane (up to 3%) was reported to decrease myocardial contraction and oxidative stress, the common symptoms of coronary heart diseases, in Zucker diabetic fatty rats [ 34 ]. When general inflammation was induced by Zymosan in mice, a subanesthetic dose of isoflurane (0.7%) increased the survival rate from 10% to 45% and reduced inflammation by upregulating antioxidant enzymes such as superoxide dismutase and catalase in blood and lung tissue.…”
Section: The Effect Of Isoflurane and Sevoflurane On Oxidative Strmentioning
confidence: 99%
“…Regarding the studies carried out to relate both drugs to ROS production, paradoxically. it has been observed that they may be involved in the beneficial effects of volatile anesthetics used in preconditioning [103,104].…”
Section: Role Of Halogenated Agents During Cardiac Surgerymentioning
confidence: 99%